2011
DOI: 10.1111/j.1460-9568.2010.07551.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and clinical effects of short-term hand immobilisation

Abstract: In this work, functional changes in the sensorimotor cortex following unilateral hand immobilisation were investigated in 11 healthy volunteers. Sensory and motor function of both hands was also assessed. Cortical activation was monitored with functional magnetic resonance imaging at 3 T. All examinations were performed prior to and directly after 72 h of immobilisation of the dominant hand and wrist. Following unilateral immobilisation, cortical activation increased substantially during tactile stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
5
22
2
1
Order By: Relevance
“…While previous studies have shown symmetric effects between the two hemispheres on motor and somatosensory domains after the non-use of one limb and the consequent overuse of the free one (Lissek et al, 2009;Avanzino et al, 2011;Weibull et al, 2011), with the present results an asymmetry emerges. We found that PPS boundaries contracted around the non-used arm, but did not change around the overused limb (Exp.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…While previous studies have shown symmetric effects between the two hemispheres on motor and somatosensory domains after the non-use of one limb and the consequent overuse of the free one (Lissek et al, 2009;Avanzino et al, 2011;Weibull et al, 2011), with the present results an asymmetry emerges. We found that PPS boundaries contracted around the non-used arm, but did not change around the overused limb (Exp.…”
Section: Discussioncontrasting
confidence: 79%
“…Thus, we evaluated two opposite effects: the non-use of the right arm and the concurrent overuse of the left limb. In line with previous studies, the two different effects were evaluated separately for both sides (Avanzino et al, 2011;Lissek et al, 2009;Weibull et al, 2011).…”
Section: Preliminary Notementioning
confidence: 98%
“…Huber et al (2006) and Moisello et al (2008) both reported that 12 hours of left arm immobilisation produces increased normalised hand-path area and variability during out-and-back movements. Furthermore, Weibull et al (2011) reported that 3 days of right hand immobilisation produces deficits in fine motor dexterity (assessed using the Purdue pegboard) and Ngomo et al (2012) showed that 4 days of immobilisation of the non-dominant hand significantly impedes the ability to acquire a novel motor task. Within the current study, both groups demonstrated motor learning by increasing the number of pegs placed within each session, suggesting that motor performance improved with training irrespective of immobilisation.…”
Section: Motor Performance Is Impaired Following Immobilisationmentioning
confidence: 99%
“…Whereas most studies of limb immobilization are complicated by their purpose in treating orthopedic injuries, a few studies have been performed in healthy volunteers for periods up to 3 wk (Clark et al 2008(Clark et al , 2010Lundbye-Jensen and Nielsen 2008;Weibull et al 2011). Immobilization resulted in significant reduction in contraction torque and strength and alteration of neurophysiological properties, requiring ϳ1 wk for recovery.…”
Section: Adverse Consequences Of Limb Immobilizationmentioning
confidence: 99%
“…Immobilization resulted in significant reduction in contraction torque and strength and alteration of neurophysiological properties, requiring ϳ1 wk for recovery. Even short-term casting (72 h) resulted in changes in grip strength, dexterity, and tactile discrimination (Weibull et al 2011). Nevertheless, casting up to 3 wk in duration is deemed benign, and any functional deficits are typically transient.…”
Section: Adverse Consequences Of Limb Immobilizationmentioning
confidence: 99%